2011
DOI: 10.2308/aud.2011.30.1.149
|View full text |Cite
|
Sign up to set email alerts
|

Internal Audit Sourcing Arrangements and Reliance by External Auditors

Abstract: SUMMARY: A company’s internal audit (IA) function can be maintained in-house, outsourced to an IA service provider, or cosourced (a combination of the in-house and outsourced IA functions). This study explores the effect of these sourcing arrangements on the external auditor’s assessed quality and reliance on the IA function. We predict that external auditors consider the cosourced and outsourced IA functions to be equal in terms of assessed quality and reliance. Furthermore, we predict that the external audit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
84
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 17 publications
3
84
0
4
Order By: Relevance
“…an auditing or accounting firm) tends to comply more with MFRS 7 as compared to firms that have their own in-house internal audit functions. This is consistent with prior studies (see Desai et al 2011;Abdolmohammadi 2013) but contradicts with the revised MCCG (2012) recommendations. The revised MCCG (2012) states that companies should establish an internal audit function as one of the mechanisms to recognise and manage the risk.…”
Section: Internal Audit Functions (Ia)supporting
confidence: 89%
See 2 more Smart Citations
“…an auditing or accounting firm) tends to comply more with MFRS 7 as compared to firms that have their own in-house internal audit functions. This is consistent with prior studies (see Desai et al 2011;Abdolmohammadi 2013) but contradicts with the revised MCCG (2012) recommendations. The revised MCCG (2012) states that companies should establish an internal audit function as one of the mechanisms to recognise and manage the risk.…”
Section: Internal Audit Functions (Ia)supporting
confidence: 89%
“…As normally, firms would outsource their internal audit functions to a professional service provider, who can provide specialised resources, and thus be able to strengthen the internal control of the firms. Similarly, a study by Desai, Gerard and Tripathy (2011) found that external auditors assess the quality of outsourced IAF to be higher than the quality of an in-house IAF and thus are more willing to rely (to a greater extent) on outsourced IAF than in-house IAF. Accordingly, the study predicts that firms that outsource their internal audit functions are more likely to comply with MFRS requirements, given firms would outsource their internal audit functions to a professional service provider (i.e.…”
Section: Internal Audit Functions (Ia)mentioning
confidence: 97%
See 1 more Smart Citation
“…La satisfaction des auditeurs externes au regard des travaux antérieurs de la fonction d'audit interne s'est ajoutée à la liste des indicateurs de la compétence des auditeurs internes, ce qui reflète le dynamisme de la relation entre les auditeurs externes et internes (Brown et Karan, 1986). Les résultats obtenus par Desai, Gerard et Tripathy (2011) ont montré que les auditeurs externes considèrent que, dans l'ensemble, la compétence de l'audit interne est jugée plus grande si cette fonction fait appel à des consultants externes pour réaliser les travaux en partie ou en totalité, car ces derniers sont considérés comme des experts. Cependant, l'étude menée par Munro et Stewart (2010) indique le contraire.…”
Section: Les Critères De Compétence Des Auditeurs Internesunclassified
“…Outsourced internal audit refers to internal audit services that are undertaken by independent accounting firms (Carcello, Hermanson & Raghunandan, 2005;Desai, Gerard & Tripathy, 2011). According to Bursa Malaysia, listed companies are required to disclose whether their internal audit function is performed in-house or is outsourced.…”
Section: Sourcing Arrangement Of Internal Audit Functionmentioning
confidence: 99%